영화 속 흡연 장면에 대한 탐색적 연구: 2000-2013년에 국내에서 개봉된 흥행영화에 대한 내용분석 - 정민수; Jung, Minsoo (保健敎育健康增進學會誌, 2014)
Objectives: While cinema is regarded in the contemporary popular leisure activities, the presentation smoking scenes in films has not been fully studied. We investigated Korean box-office hit movies by using content analysis. Methods: We sampled fifty-one hit films played in Korean cinemas during the period 2000-2013. Here, a hit film is defined as a movie viewed by at least 5,000,000 audiences. Results: We found that 78.1% of the Korean hit films contained smoking scenes, whereas only 15.6% of the American hit films were so. Films with the more frequent number of smoking scenes could be lined up in the order of crime, thriller, and action genres (p<.05). Smoking actors were leading roles, hence attractive characters appealing to the audience. Moreover, the smoking rate of female characters in the films was determined to be 3.66 times greater than the actual smoking rate of females in reality. Conclusions: Smoking scenes are likely to affect the audiences' cognitive priming and/or social learning with respect to smoking. Therefore, it would be necessary to set a restriction standard to the frequency of smoking scenes to appear Korean films, and to consider it as an important factor in the assigning a screening grade to such films.